Again and again : a novel - Evison, Jonathan (New York : Dutton, 2023)
"Geno is living out his final days in a nursing home, bored, curmudgeonly, and struggling to connect with his nursing assistant, Angel, who he sees as being different from him in every way possible, and unable to understand him in any way. Perhaps no one really can, since Geno has been telling everyone who will listen that he's not just Geno-in fact, he's lived many past lives, dating back 1000 years, and since that first life in Seville, Spain, he has been searching for the love of his life he met then and only one other time since. Is this possible-was his life a miraculous one that let him live, again and again? Or is he crazy, or lonely, rehearsing larger-than-life fantasies to get through the day?"--
Keywords: Older people -- Fiction; Reincarnation -- Fiction; Interpersonal relations -- Fiction; Love -- Fiction; Nurses' aides -- Fiction; Nursing home residents -- Fiction; Historical fiction; Psychological fiction